Efektivitas Penerapan Sistem Elektronifikasi Transaksi terhadap Penyerapan Belanja Barang dan Jasa pada Sekretariat Daerah Kota Palembang - Putri, Sherina Dwi; Periansya, Periansya; Sari, Yuliana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the Effectiveness of the Implementation of the Transaction Electronification System on the Absorption of Goods and Services Expenditures at the Palembang City Regional Secretariat. This type of research is quantitative research. The sample used in this study amounted to 47 civil servants in the financial planning section of the Palembang City Regional Secretariat. The type of data used is primary data with a simple linear analysis method. The sampling technique used saturated sampling technique. The results of this study indicate that the variable Effectiveness of Transaction Electronification System Implementation has a positive and significant effect on the variable Absorption of Goods and Services Expenditure. Keywords: Effectiveness, Transaction Electronification System, Goods and Services Expenditure